2009
DOI: 10.2174/138920109789069332
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking of Mature miRNA-122 into the Nucleus of Live Liver Cells

Abstract: The binding of superquencher molecular beacon (SQMB) probes to human single-stranded cellular miRNA-122 targets was detected in various single live cells with femtosecond laser microscopy. For delivery of the SQMB-probes, 3D-nanoprocessing of single cells with sub-15 femtosecond 85 MHz near-infrared laser pulses was applied. Transient nanopores were formed by focusing the laser beam for some milliseconds on the membrane of a single cell in order to import of SQMB-probes into the cells. In single cells of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 32 publications
1
55
0
Order By: Relevance
“…A number of reports have described the occurrence of particular miRNAs in animal cell nuclei and nucleoli (Hwang et al 2007a;Kim et al 2008;Marcon et al 2008;Ohrt et al 2008;Place et al 2008;Foldes-Papp et al 2009;Politz et al 2009;Liao et al 2010). In this article, we wished to evaluate the generality of miRNA nuclear localization by assaying a nontumor, minimally passaged, progenitor cell line.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of reports have described the occurrence of particular miRNAs in animal cell nuclei and nucleoli (Hwang et al 2007a;Kim et al 2008;Marcon et al 2008;Ohrt et al 2008;Place et al 2008;Foldes-Papp et al 2009;Politz et al 2009;Liao et al 2010). In this article, we wished to evaluate the generality of miRNA nuclear localization by assaying a nontumor, minimally passaged, progenitor cell line.…”
Section: Discussionmentioning
confidence: 99%
“…While miRNAs generally function in the cytoplasm, mature miRNAs have been found in the nucleus, and, in some cases, shown to alter promoter activity (Hwang et al 2007a;Kim et al 2008;Marcon et al 2008;Ohrt et al 2008;Place et al 2008;Foldes-Papp et al 2009). Other miRNAs have been localized to the nucleolus (Politz et al 2009;Liao et al 2010) and, notably, the nuclear and nucleolar abundances of some miRNAs have been reported to be greater than their cytoplasmic levels.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs), 5 a class of 19 -24-nucleotide noncoding RNAs (ncRNAs), are widely involved in post-transcriptional gene regulation (1). According to the canonical model, miRNAs recognize target mRNAs and exert their roles predominantly in the cytoplasm.…”
mentioning
confidence: 99%
“…Accumulating evidences, however, have demonstrated that certain mature miRNAs can reenter the nucleus (2-4). Földes-Papp et al (5) were the first to report the expression of miR-122 in liver cells and show unequivocal proof for the relocation of cytoplasm-assembled single-stranded miR-122 into the cell nucleus. Hwang et al (4) demonstrated that miR-29b could be imported into the cell nucleus.…”
mentioning
confidence: 99%
“…Recently, it has been evidenced that mature microRNAs may also be localized in nucleus, through a specific hexanucleotide (AGUGUU) sequence which acts as a transferable nuclear localization element [24]. An example of this is the positive regulatory effect on transcriptional level of mir-122 in liver cells [25]. Moreover, it has been shown that vesicles of endocytic origin known as exosomes may contain both mRNA and microRNAs, which can be delivered to adjacent cells, and can be functional therein.…”
Section: Micrornas Biogenesismentioning
confidence: 99%